Canonic techniques in the caccia: compositional strategies and historical development. Issue 2 (3rd September 2014) - LOPATIN, MIKHAIL
ABSTRACT Canonic techniques in the Trecento caccia reveal a wide spectrum of ostinato procedures ranging from brief cadence patterns to large-scale harmonic and/or melodic repetition schemes. The ostinato phenomenon is thus an important structural component of canonic technique in the caccia. This article examines these ostinato patterns in terms of a putative historical and structural transformation of the genre at the intersection of unwritten and written practices. Special emphasis is placed on the definition of the caccia from the anonymous Trecento treatise, Capitulum de vocibus applicatis verbis, and its correlation with the early layer of the caccia repertoire.